2018
DOI: 10.1093/jxb/ery040
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between the unfolded protein response and reactive oxygen species: a dynamic duo

Abstract: Secretory proteins undergo modifications such as glycosylation and disulphide bond formation before proper folding, and move to their final destination via the endomembrane system. Accumulation of unfolded proteins in the endoplasmic reticulum (ER) due to suboptimal environmental conditions triggers a response called the unfolded protein response (UPR), which induces a set of genes that elevate protein folding capacity in the ER. This review aims to establish a connection among ER stress, UPR, and reactive oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 127 publications
0
72
0
Order By: Relevance
“…However, excessive quantities of ROS can result in damage to proteins, modifying their function and disrupting ER homeostasis [ 27 , 32 , 34 , 73 ]. ROS overproduction can be sensed by the ER, which is highly sensitive to changes in ROS levels through redox sensors, such as, for example, the thiol groups of cysteines [ 33 , 70 , 74 , 75 , 76 , 77 ], causing misfolded protein accumulation and consequently increasing ROS production, which leads to a vicious cycle able to activate UPR, generate chronic stress, and induce apoptosis [ 32 , 33 , 34 , 70 , 72 ]. Moreover, ROS overproduction causes a decrease in the GSH/GSSG ratio and in antioxidant enzyme levels, whilst oxidizing lipids, DNA, and proteins [ 19 , 20 , 21 , 22 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, excessive quantities of ROS can result in damage to proteins, modifying their function and disrupting ER homeostasis [ 27 , 32 , 34 , 73 ]. ROS overproduction can be sensed by the ER, which is highly sensitive to changes in ROS levels through redox sensors, such as, for example, the thiol groups of cysteines [ 33 , 70 , 74 , 75 , 76 , 77 ], causing misfolded protein accumulation and consequently increasing ROS production, which leads to a vicious cycle able to activate UPR, generate chronic stress, and induce apoptosis [ 32 , 33 , 34 , 70 , 72 ]. Moreover, ROS overproduction causes a decrease in the GSH/GSSG ratio and in antioxidant enzyme levels, whilst oxidizing lipids, DNA, and proteins [ 19 , 20 , 21 , 22 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under acute ER stress, glucose-related protein 78 kDa (GRP78) and glucose-related protein 94 kDa (GRP94) are released from the ER membrane and activate the unfolded protein response (UPR) to restore ER functions, such as protein synthesis and transport, protein folding, lipid and steroid synthesis, among others [ 27 , 28 , 29 , 30 , 31 ], in addition to the antioxidant response and autophagy [ 27 , 32 , 33 , 34 ], which maintain cellular homeostasis. However, if the ER stress is excessive or chronic and cannot be corrected, UPR signaling promotes apoptosis [ 29 , 31 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mammalian cells, it is said that ER stress and ROS production are in a "vicious cycle" inducing each other (Malhotra and Kaufman, 2007). The situation in plants may be similar to animals (Ozgur et al, 2018), but that requires further testing.…”
Section: Discussionmentioning
confidence: 99%
“…As well known, ROS mediated‐stress damage is common denominator in arsenic‐induced disease 45 . A series of studies have shown that excessive accumulation of ROS has associated with the ER stress to further aggravate cell death 46‐48 …”
Section: Discussionmentioning
confidence: 99%